Exploration of Geometry Concepts in the Architecture of the Grand Mosque of Sultan Thaf Sinar Basarsyah as a Mathematics Learning Media - Putri handayani Nurmaidah; Nur Ainun Lubis (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Ethnomathematics is the study of how people from different cultures understand, interpret, and use mathematical concepts. Meanwhile, various studies have highlighted the beauty and symbolism of geometric aspects in mosque architecture, but there are still limited studies examining how these geometric elements can be used as learning media. This study aims to explore geometric concepts in the architecture of the Sultan Thaf Sinar Basarsyah Grand Mosque and examine its application as a contextual mathematics learning resource. The methods used include direct observation, semi-structured interviews, and visual documentation with a descriptive qualitative approach. This study uses an interactive model data analysis technique proposed by Miles and Huberman (1994). The results show that the mosque building contains geometric elements such as circles, semicircles, squares, rectangles, rhombuses, and cylinders that have cultural symbolic meaning and religious aesthetics. This study recommends that mathematics learning increasingly utilize architectural heritage as an interesting and educational learning medium, thereby strengthening cultural identity while supporting the development of mathematical conceptual abilities in a more contextual and meaningful manner.